Determination Of The Suspect Of Decency Crime In Police Resort Kudus (Case Study in the PPA Police Kudus) - Bonar Setyantono (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Act No. 17 of 2016 concerning Second Amendment Act No. 23 of 2002 on the Protection of Children into the law on protection of children. The Criminal Code decency criminal acts against children stipulated in the Criminal Code in Chapter XIV of Article 287, Article 289, Article 290, Article 292, Article 293, Article 294, Article 295 and Article 296 of the Criminal Code. Sanction criminal acts of decency against Children in the Child Protection Act provided for in Article 81, 81A and 82, it is as chapter to ensnare AD bin SPT has committed the crime of DSH.Determination Mechanism Crime Suspect Actor of Decency, a complaint go to the police station, Disposition down unit further women's and children Women and Children Services Unit conducted an investigation. Investigations completed his case to determine whether the elements of a criminal offense are met, if the elements are met and the initial evidence, then the police can determine the suspect's Women and Children Unit subsequently conducted investigation against the suspect to complete the examination of the case file. Barriers or obstacles, namely victims and their families did not immediately report to the police, in providing materially incomplete, the loss of evidence and the suspect fled. Solutions to overcome obstacles or barriers that Police (Policewoman) conduct a personal approach to the victim with the intention of victims give full details, the investigators provide a special place to do the investigation, victims and their families can request legal considerations with the investigator, with the purpose of the case is not protracted and can be immediately handled.Take quick decisions to prevent criminals escaping decency.Keywords: Determination of the Suspect; Decency Criminal Acts and Children.